Salivary Statherin as a Dental Caries Biomarker among a Sample of Adolescents in Baghdad City - Yousif, Sara Hikmat; Qasim, Alhan Ahmed (AL-Kindy College Medical Journal, 2024)
Background: Dental caries represents a multifaceted disease impacting teenagers across the globe. A combination of factors, including fermentable carbohydrates, acid-producing bacteria, saliva, and host-related characteristics, influences its development. Salivary statherin controls microorganisms by aggregating them and preventing them from adhering to hard tissue and epithelium. Salivary statherin may maintain tooth integrity.Objective: This research investigated the potential of salivary statherin as a biomarker for dental caries, examining its connection to the nutritional status of adolescents.Subjects and Methods: This comparative (observational) research included 90 15-year-old adolescents of both sexes. Participants were divided into two distinct groups: 30 individuals without caries, serving as the control group, and 60 individuals with caries, referred to as the study group. Following the World Health Organization guidelines, adolescents with varying caries experiences were further categorized. Thirty of them exhibited a moderate level of caries, with 1 to 3 affected teeth, while the remaining thirty were classified as having severe caries, with a Decay-Missing-Filled Teeth (DMFT) score greater than 10. The DMFT Index measured caries experience. Salivary statherin analysis from unstimulated saliva. Height, weight, and body mass index measured nutrition, classifying adolescents as normal weight, overweight, or obese.Results: Statherin levels decreased with the severity of caries increasing. There was a significant result in the overweight, healthy, and total sample among caries severity groups (P value